An Analysis of English Teacher in Learning Assessment at SMP Negeri 3 Mare - Astuti, Asriani; Qalby, Nur; Muhsin, Muh Arief (FKIP Unismuh Makassar, 2023)
This study aims to analyze the types of assessments used by teacher in teaching English to grade nine at SMP Negeri 3 Mare Kab Bone and to determine the use of these assessments by teacher. This study used a qualitative method. The subjects of this study were English teacher at SMP Negeri 3 Mare. In analyzing the data, the researcher collected data from observation, interview, and gave questionnaire to teacher, and identified the types of assessment used by teacher in teaching English and how to use these assessments in teaching English. The results show that teacher use authentic assessment in teaching English. There are three types of assessment in teaching. These assessments are skills assessment, portfolio assessment, and project assessment and for project assessment the teacher does not use them in teaching activities because it takes longer time, so the teacher only gives assignments to students in the form of project assignments to be completed at home as project assignments. for the final exam The researcher concluded that the types of assessment used by the teacher in teaching English were skills assessment and project assessment on authentic assessment in teaching English at SMP Negeri 3 Mare.